Webinar Kesehatan Mental “Menghadapi Quarter Life Crisis” Sebagai Upaya Meningkatkan Mental Health Awareness pada Remaja - Bagas Rahmatullah (Publikasi Indonesia, 2022)
Mental health is an important aspect in human beings. The prevalence of anxiety disorders in adolescents around the world is around 20.5%, while depression is around 25.2% worldwide (Racine et al., 2021). According to Robbins and Wilner (2001) there are other problems that teenagers often experience, namely the Quarter Life Crisis phenomenon, which is a condition where adolescents begin to feel indecisive in making decisions, worry about their interpersonal relationships, feel anxious about the future, feel pressured by the situation, judgments emerge. negative self, and feeling hopeless. Kampuskoe is collaborating with researchers to hold an activity to jointly provide education about mental health in adolescents. This activity involved 128 participants. All participants were satisfied in participating in all existing activities. In the future, this kind of activity can be carried out with a larger number of participants so that more youth will gain an understanding of mental health.